Tindak Pidana Korupsi yang Dilakukan oleh Karyawan Badan Usaha Milik Negara - I Putu Agus Sudiyasa Putra; Ida Ayu Putu Widiati; I Made Minggu Widyantara (Fakultas Hukum Universitas Warmadewa, 2021)
The crime of corruption to date has spread to all sectors of the government, even to state-owned companies. From the description of the background, the purpose of the study is to understand the regulation of corruption crimes committed by employees of the state-owned enterprises and to know criminal responsibility for corruption crimes committed by employees of state-owned enterprises. The research method is a normative legal research type with a statutory and conceptual approach. Analysis of legal materials using legal arguments in the form of deductive inductive legal logic. The results of the study show that corruption is regulated in Law 20/2001 regarding amendments to Law 31/999 concerning the Eradication of Corruption Crimes. Corruption crimes generally involve a group of people who mutually enjoy the benefits of the crime. This element is the purpose of the maker in committing acts of abusing the authority, opportunities or facilities available to him because of his position or position, namely to benefit himself or another person or a corporation. Accountability for criminal acts of corruption committed by BUMN employees by applying punishment in accordance with article 20 paragraph (7) of the UUPTK in the form of a criminal fine with the maximum provisions plus 1/3 and additional penalties in accordance with article 18 paragraph (1) and paragraph (2).